Importance of Productivity Work: Employees at Cooperatives Save Baitul Maal Sharia Loans and Financing Wat Tamwil Surya Madani - Hidayah, Khofifah Nur; Astuti, Evi Risdiyanti; Lestari, Novita (Journal of Economic, Religious, and Entrepreneurship (JoERE), 2024)
All business and organisations must own desired goal achieved. For reach, aim at a company that needs a factor source: Power Man. Source Power productive human is source Powerful humans who have high productivity, work hard to achieve the target already set by A company, and are capable of finishing tasks within the appropriate time. Employees, as part of the company, have a role important in determining the success of the company in terms of implementation duties and functions carried out. The purpose of doing it is to study This will benefit the readers in terms of information productivity. Workers at sharia institutions, especially cooperatives, save sharia loans and finance Baitul Maal Wat Tamwil Surya Madani Boyolali. Study This is qualitative-descriptive with a qualitative method and uses descriptive analysis via interviews and observations. In improving productivity, work environment, work, and family environment are influential. Motivation from employees is also influential on target achievement. Management productivity Work employees are managed through regulations, managing work stress, education, and training.